A new approach to cardiac fat volume assessment and the correlation with coronary artery calcification - Torkian Pooya; Langroudi Taraneh Faghihi; Negarestani Amir Masoud; Shabestari Abbas Arjmand; Naderian Mohammadreza; Tabary Mohammadreza; Khaheshi Isa (Sciendo, 2020)
Background. Coronary artery disease (CAD) is the foremost cause of death in the most developed societies. Plaque formation in epicardial coronary arteries and ensuing inflammation are a known pathophysiologic factor of CAD.